An automatic compensation method for improving forming precision of multi-layer multi-bead component. (June 2021) - Zhao, Tao; Liu, Haihua; Li, Liangyu; Liu, Wenji; Yue, Jianfen; Wang, Tianqi; Liu, Haobo
Wire and arc additive manufacturing (WAAM) is a promising technology for manufacturing large-sized metal components. However, the material shortage region (MSR) at the edge of each slicing layer can influence the forming precision and surface flatness of components. To solve these problems, this paper proposes a shape follow-up edge cycle compensation (SECC) method and model for predicting the weld width and weld height to improve the efficiency of the WAAM process. First, the prediction model was used to determine the weld width and weld height for various welding parameters. The predicted width was then used to obtain the optimal overlap distance, and the filling path of each layer was generated. The same weld height was used for slicing of the 3D model and the tool path compensation cycle was generated. Second, the influence of the MSR on the morphology of multi-layer multi-bead (MLMB) components was analyzed. The MSR results in a height difference between the edge height and the middle height of every deposited layer, and the height difference increases as more layers are added and the height of the component increases. Furthermore, the influence of the MSR gradually extends from the edge to the middle, such that the upper surface presents a parabolic shape. Finally, a mathematical model was established to determine the height difference based on the area of the MSR. When the height difference reaches the weld height, an edge compensation weld is added to eliminate the height difference. Our experimental results show that the proposed forming control strategy improves forming precision and surface flatness. The method is highly feasible and can be applied to a wide range of WAAM applications.